ROLE OF THE OBJECTS OF CULTURAL HERITAGE IN THE STUDY OF THE HISTORY OF UZBEKISTAN ( on the example of Kokand city) (Scientific journal of the Fergana State University, 2023)
The article shows the role of cultural heritage objects in the study of the history of Uzbekistan using the example of the city of Kokand. The issue is analyzed within the framework of some architectural structures of the times of the Kokand Khanate and the period of colonial dependence on the Russian Empire.